Family, gold and power: The plots of kinship. San Juan (1790-1815). - Fracapani Ríos, Eliana Beatriz (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The purpose of this paper is to present the families dedicated to the mining activity and explain how family networks were woven, in order to interpret the power structure, the accumulation of capital, and the form in which production relations were articulated, at the end of the colonial period, in the territory of the current province of San Juan. In order to do this, irst-hand sources such as scribe protocols, testaments and judicial records are used.